2017
DOI: 10.1016/j.ygyno.2017.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal disease dissemination patterns are associated with residual disease, extent of surgery, and molecular subtypes in advanced ovarian cancer

Abstract: Objective To investigate the association between intraperitoneal (IP) disease dissemination patterns, residual disease (RD), surgical complexity, and molecular subtypes in advanced high-grade serous ovarian cancer (HGSOC). Methods 741 patients with operable stage III–IV HGSOC undergoing primary debulking surgery at Mayo Clinic from 1994–2011 were categorized into four mutually exclusive IP disease dissemination patterns: upper abdominal (60%), miliary (16%), lower abdominal (15%), and pelvic (9%). Surgical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…Molecular classification of high-grade serous ovarian cancer (HGSOC) using tumor mRNA profiling was first described by Tothill et al [1] and has been independently confirmed by multiple studies, including our own [2,3]. We subsequently demonstrated that molecular subtypes are associated with intraperitoneal (IP) disease dissemination patterns and surgical outcomes in advanced HGSOC [2][3][4]. The relationship between molecular subtype, dissemination patterns, and residual disease (RD) is complex.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…Molecular classification of high-grade serous ovarian cancer (HGSOC) using tumor mRNA profiling was first described by Tothill et al [1] and has been independently confirmed by multiple studies, including our own [2,3]. We subsequently demonstrated that molecular subtypes are associated with intraperitoneal (IP) disease dissemination patterns and surgical outcomes in advanced HGSOC [2][3][4]. The relationship between molecular subtype, dissemination patterns, and residual disease (RD) is complex.…”
Section: Introductionmentioning
confidence: 64%
“…Patients with borderline tumors, those who were treated with neoadjuvant chemotherapy, and those without research consent or molecular profiling were excluded. IP disease dissemination patterns among eligible patients with stage III and stage IV HGSOC were defined into four categories using our previously published criteria [4]: pelvic disease, lower abdominal disease, upper abdominal disease, and miliary disease (Supplementary Table S1). Four RD groups were defined, RD0, RD 0.1-0.5 cm, RD 0.6-1.0 cm, RD N1 cm, based on the largest residual tumor diameter.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations